Pathogen reduction diminishes the protective effects of platelets on endothelial barrier permeability in vitro - Alison B. Nair; Byron Miyazawa; Alpa Trivedi; Lindsay Vivona; Alexander Fields; Kimberly Herrera; Lucy Z. Kornblith; Joseph Cuschieri; Shibani Pati (Blood Vessels, Thrombosis & Hemostasis, 2025)
Abstract: Platelet transfusion not only attenuates bleeding and promotes hemostasis but also plays a critical role in vascular stability and endothelial barrier integrity. Under amotosalen-UVA pathogen reduction of platelets, pathogen nucleic acids undergo adduction, which prevents their replication and greatly reduces the risk of transfusion-transmitted infections. Although pathogen-reduced (PR) platelets are increasing in clinical use, the physiologic effects of pathogen reduction on platelets, particularly its impact on platelet-endothelial interactions, have yet to be described. This study compared PR platelets with nonpathogen-reduced (NPR) platelets in measures of effect on endothelial permeability in vitro. We hypothesized that PR platelets would be similar to NPR platelets. However, in endothelial cell immunohistochemistry and impedance assays, PR platelets demonstrated a significantly diminished capacity to attenuate endothelial barrier permeability at early storage time points. This small but significant difference requires further mechanistic and clinical study to understand its implications, particularly in patients with bleeding with vascular fragility.